2011
DOI: 10.1152/ajpcell.00502.2010
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor and metastasis: calcium-independent phospholipase A2β deficiency protects against breast cancer metastasis to the lung

Abstract: We determined the contribution of calcium-independent phospholipase A(2)β (iPLA(2)β) to lung metastasis development following breast cancer injection into wild-type (WT) and iPLA(2)β-knockout (iPLA(2)β-KO) mice. WT and iPLA(2)β-KO mice were injected in the mammary pad with 200,000 E0771 breast cancer cells. There was no difference in primary tumor size between WT and iPLA(2)β-KO mice at 27 days postinjection. However, we observed an 11-fold greater number of breast cancer cells in the lungs of WT mice compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 57 publications
0
36
0
1
Order By: Relevance
“…GPx inhibits cisplatin-induced apoptosis via the downregulation of Bcl2 in H460 human lung cancer cells [42]. iPLA2 also contributes to lung metastasis by stimulating plateletactivating factor production [43]. Recently, we also reported that GPx and iPLA2 activities were increased by PRDX6 in lung tumor tissues [19,32].…”
Section: Discussionmentioning
confidence: 93%
“…GPx inhibits cisplatin-induced apoptosis via the downregulation of Bcl2 in H460 human lung cancer cells [42]. iPLA2 also contributes to lung metastasis by stimulating plateletactivating factor production [43]. Recently, we also reported that GPx and iPLA2 activities were increased by PRDX6 in lung tumor tissues [19,32].…”
Section: Discussionmentioning
confidence: 93%
“…Nude mice bearing PRDX6-overexpressing lung cancer cells exhibited increases in tumor size and weight and increased expression of both GPx and iPLA 2 ␤ , and these outcomes were inhibited when a mutant PRDX6 was used, suggesting that PRDX6 promotes lung tumor growth via GPx and iPLA 2 ␤ . Occurrence of breast cancer is often accompanied by metastasis to the lung and injection of E0771 breast cancer cells in the mouse mammary pads resulted in an 11-fold higher number of breast cancer cells in WT lungs, relative to lungs from iPLA 2 ␤ -null mice ( 377 ). Further, production of thrombin-stimulated platelet-activating factor in lung endothelial cells was increased in the WT lungs and absent in the iPLA 2 ␤ -null mice.…”
Section: Ipla 2 ␤ and Diseasesmentioning
confidence: 98%
“…PGE 2 is derived from the metabolism of membrane phospho lipids, through the action of phospholipase A 2 (PLA 2 ). Both Ca 2+ dependent PLA 2 (cPLA 2 ) and Ca 2+ independent PLA 2 (iPLA 2 ; also known as PLA2G6) 6 cleave phosphatidyl choline into arachidonic acid and lyso phosphatidylcholine (FIG. 1).…”
mentioning
confidence: 99%